Beam studies of the segmented resistive WELL: a potential thin sampling element for digital hadron calorimetry - Arazi, Lior (2013)
Thick Gas Electron Multipliers (THGEMs) have the potential of constituting thin, robust sampling elements in Digital Hadron Calorimetry (DHCAL) at future colliders. We report on recent beam studies of new single- and double-THGEM-like structures: the multiplier is a Segmented Resistive WELL (SRWELL) – a single-faced THGEM in contact with a segmented resistive layer inductively coupled to readout pads. Several 10×10 cm2 configurations with a total thickness of 5–6 mm (excluding electronics) with 1 cm2 pads were investigated with muons and pions. The pads were coupled to a scalable readout system APV chip, APV-SRS (Raymond et al. [22]). Detection efficiencies in the 98% range were recorded with an average pad-multiplicity of ~1.1. The resistive anode resulted in efficient discharge damping, with potential drops of a few volts; the discharge probabilities were ~10−7 for muons and ~10−6 for pions, at rates of a few kHz/cm2 and for detectors in the double-stage configuration. Further optimization work and research on larger detectors are underway.